On feeling good at work: the role of regulatory mode and passion in psychological adjustment. Issue 6 (1st December 2014) - Bélanger, Jocelyn J.; Pierro, Antonio; Kruglanski, Arie W.; Vallerand, Robert J.; De Carlo, Nicola; Falco, Alessandra
Abstract The major postulate of this work is that regulatory modes influence the type of passion people experience with regard to an activity, which in turn influences their psychological adjustment. Integrating regulatory mode theory and the dualistic model of passion, we hypothesized that locomotion—associated with intrinsic and autonomous motivations—would positively predict harmonious passion, which in turn would enhance workers' psychological adjustment. In contrast, we hypothesized that assessment—associated with extrinsic and non‐autonomous motivations—would positively predict obsessive passion, which in turn would reduce workers' psychological adjustment. Two field studies supported these hypotheses with psychological adjustment measures of stress (Study 1) and burnout (Study 2) in different work contexts.